The novel : a survival skill - Parks, Tim (Literary agenda., 2015)
'The novel: a survival skill' offers a completely new account of the relationship between writer, text, and reader. Drawing on ideas from systemic psychology and positioning theory, Parks suggests that both the content and style of a novelist's work, the kind of stories told, and the way in which they are told, form part of a more general strategy of suvival that the novelist has developed in reaponse to tensions within his or her family of origin. Radically undermining traditional lit-crit criteria, and deconstructing the pieties with which the novel is usually defended, Parks gives a novelist's own insider account of what may be best understood as the biography of the act of writing itself and its relation to the lives with which it is entwined.